Influences of silicon-rich shallow trench isolation on total ionizing dose hardening and gate oxide integrity in a 130 nm partially depleted SOI CMOS technology. (July 2017) - Song, Lei; Hu, Zhiyuan; Zhang, Mengying; Liu, Xiaonian; Dai, Lihua; Zhang, Zhengxuan; Zou, Shichang
Abstract: The influences of silicon-rich shallow trench isolation (STI) on total ionizing dose (TID) hardening and gate oxide integrity (GOI) in a 130 nm partially depleted silicon-on-insulator (SOI) complementary metal-oxide semiconductor (CMOS) technology are investigated. Radiation-induced charges buildup in STI oxide can invert the parasitic sidewall channel of the n-channel transistor, which will increase the off-state leakage current and decrease the threshold voltage for the main transistor. Compared with the general STI process, the silicon-rich STI process can significantly suppress the increase in leakage current and negative shifts in subthreshold region induced by the total dose radiation, implying TID hardening for STI trench oxide. However, the silicon-rich STI process has a deleterious impact on GOI. It leads to the thin gate oxide thickness at trench corner and lowers the gate oxide breakdown voltage. Issues of gate oxide integrity induced by silicon-rich STI are investigated in this paper, and an optimized process to solve this problem is proposed and examined. Finally, the TID response of the optimized silicon-rich STI process is presented in comparison to the general and silicon-rich STI processes. Highlights: A silicon-rich shallow trench isolation (STI) process is proposed. The silicon-rich STI shows total ionizing dose radiation hardening. This process should be optimized to assure the gate oxide integrity.